Musculoskeletal disorders among offshore-structure fabrication yard workers - Ch’Ng Emily, Huey Ling (2010)
Many researches in the area of ergonomics are focused on musculoskeletal disorders (MSDs) among workers in various line of work such as manufacturing, agriculture and construction. However, there is very little research done on MSDs among workers in heavy industries. The intention of this study is to establish the prevalence of MSDs among offshore-structure fabrication yard workers. A cross-sectional study was conducted among 132 yard workers. Preliminary direct observation on the workers general working conditions were carried out. Data on MSD symptoms of pain/discomfort were then collected via modified Standardized Nordiq questionnaires with some additional questions on the risk factors related to work-related MSDs. Overall, there are 82 (62.1%) workers who reported pain/discomfort and 50 (37.9%) others without pain/discomfort. Out of the 82 workers who had pain/discomfort within the last 12 months, 39% are welders, 9.8% are grinders, 18.3% are fitters, 7.3% are riggers, 8.5% are crane operators, 3.7% are helper welders and 13.4% are foreman and supervisors. The highest area reported of pain/discomfort is at the low back/waist (41.7%), followed by shoulder (18.9%) and neck (16.7%). Repetitive movement (OR =3.050) and bending (OR=2.417) are significant predictors of low back pain/discomfort. In conclusion, some ergonomic suggestions were provided to reduce to risks of MSDs in the workplace.